2022
DOI: 10.1002/jcaf.22586
|View full text |Cite
|
Sign up to set email alerts
|

Green business practices and corporate financialization: Role of female directors in Chinese small and medium enterprises (SMEs)

Abstract: This study examines the impact of green business practices (GBP) on firm financialization and, analyzes the moderating role of female directorship in China.A-share listed non-financial firms are sampled (total 1049 firms including 284 small and medium enterprises [SMEs]) from Shanghai and Shenzhen stock exchanges from 2009 to 2020. OLS and fixed-effects regression techniques are applied and the results show a significantly positive relationship between GBP and firms' financialization level (FIN) in the whole s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Based on the existing research, the control variables in this article include firm size, leverage ratio, Investment opportunities, Business performance, Corporate Liquidity, Shareholding of the largest shareholder, Corporate Financialization Level, Board size, Average age of directors, Female Board of Directors Ratio, Market Power of a firm and Firm Nature [ 6 , 31 , 57 , 58 ]. Detailed variable descriptions are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the existing research, the control variables in this article include firm size, leverage ratio, Investment opportunities, Business performance, Corporate Liquidity, Shareholding of the largest shareholder, Corporate Financialization Level, Board size, Average age of directors, Female Board of Directors Ratio, Market Power of a firm and Firm Nature [ 6 , 31 , 57 , 58 ]. Detailed variable descriptions are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Combing the existing literature, we find some traceable phenomena. Huang & Mirza [17] argued that green business practices can promote corporate financialization. However, this conclusion is not validated in the case of small and medium enterprises.…”
Section: Background and Motivationmentioning
confidence: 99%
“…The second trend is associated with the impact of women on boards on earnings, risk, and management (Bogdan et al 2022;Elzahar et al 2022;Guizani and Abdalkrim, 2022;Huang and Mirza, 2023;Huang and Kisgen, 2013;Levi et al 2014;Ma et al 2022;Mensah and Boachie, 2023;Neuberger et al 2023;Pucheta-Martínez et al 2016, 2018Pucheta-Martínez and Bel-Oms, 2019;Sattar et al 2022;Shauki and Oktavini, 2022;Zalata et al 2022). For example, Pucheta-Martínez et al (2016, 2018 revealed that having female institutional directors on boards can increase firm value, but if their representation exceeds a particular threshold, it may lead to a decline in firm performance.…”
Section: Background Literaturementioning
confidence: 99%
“…2022; Elzahar et al. 2022; Guizani and Abdalkrim, 2022; Huang and Mirza, 2023; Huang and Kisgen, 2013; Levi et al. 2014; Ma et al.…”
Section: Background Literaturementioning
confidence: 99%